ADVANCING THE SUSTAINABLE DEVELOPMENT GOALS THROUGH GREEN UNIVERSITIES: PROMOTING SUSTAINABLE LIFESTYLES IN THAI HIGHER EDUCATION - Hasan, Md Miran; Jin, Sun; Tran, Thao; Watcharinrat, Dowroong (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Universities are being seen more widely as key institutional actors in delivering on the SDGs by providing students with sustainability information, values and behaviour. The expansion of green university initiatives in Thailand has been seen due to rising environmental awareness and a national pledge towards sustainability. But little empirical attention provided to how institutional sustainability initiatives affect student sustainability-related lifestyles in the Thai higher education context. This research examines the potential of green universities in Thailand for environmentally responsible and sustainable livelihoods among students. Based on Theory of Planned Behavior (TPB) and an institutional context perspective, the study investigates how sustainability knowledge impacted sustainable attitudes, green campus practices, curriculum integration & student engagement and eventually sustainable lifestyle behaviours. It was a qualitative and quantitatve research design. Method: Quantitative data were collected via structured questionnaire among 100 undergraduate and postgraduate students from Shinawatra University compared with the insights from other institutions (Chulalongkorn University + Kasetsart University). Relationships between the main variables were assessed using descriptive and correlational analyses and qualitative responses given at end of survey, regarding institutional enablers and barriers to sustainable lifestyle adoption, were thematically analysed. The results show that the students tend to have positive sustainability knowledge and attitudes; but sustainable lifestyle behaviours are at a comparatively moderate level, reflecting an intention–behaviour gap. Positive associations were seen between institutional factors such as visible green campus infrastructure, indicators of curriculum integration related to sustainability and active student engagement with sustainable lifestyle practices. Qualitative results further identified poor sustainability infrastructure, lack of institutional visibility and time constraints as drivers inhibiting the behaviours. This study makes a contribution to the sustainability and higher education literature by offering empirical evidence from a Southeast Asian context, and underlining the role of institutional environments in operationalising knowledge-to-know translations into everyday behaviours. The results indicate that when coherently implemented within CESE, integrated sustainability strategies can increase the contribution of universities to SDG 4, SDG 12 and SDG 13.